Automated guided conveyor (AGC) - Nor Azzah, Abu Azmi (2010)
This project is focused on development of the control system for Automated Guided Conveyor (AGC) by using PIC 18F4550. Two approaches are proposed for this project; hardware approach where involves the development and design of AGC prototype, line follower, sensor circuit and controller circuit and software approach when the system of AGC are write by using microcode studio programmed. This project concentrates on developing the automatic system for AGC which about how the AGC will operate, involve of the movement mechanism. This prototype takes into account when AGC travel and also tries to travel in order by following the line follower. This thesis also includes the test automatic system involving test program and test circuit for the AGC before proceed to the prototype AGC control system.